ON THE INTERRELATIONSHIP OF RESULTIVE AND CAUSATIVE MEANINGS - Davlatova Mukhayyo Hasanovna (Scholar Express Journals, 2022)
The article provides a theoretical basis for the study of lexical and grammatical means of expressiveness and analyzes the well-known examples. It turned out that the resulting structures are formed differently depending on the lexical and semantic expression of the verb and the subordination of the additional argument. Attention was drawn to the resulting meanings, represented by analytical compounds in the form of verb forms, as well as to the lexical and grammatically formed resulting structures.
Keywords: aspectuality; stability; unlimited; action